CONSTRUÇÃO E VALIDAÇÃO DE TECNOLOGIA TEÓRICO-METODOLÓGICA DE GESTÃO EMPREENDEDORA - Toson, Marcelo Junior (2018)
Introduction: Overcoming traditional models and being the main character in new theoretical-methodological management approaches in nursing and health requires entrepreneurial professionals, capable of setting up innovative and systemic processes from approaches that propose a new way of thinking and acting professionally in different areas of knowledge. Taking into account the need to promote and validate new management models to consolidate the “Organization and Management of the Maternal and Children’s Care Network” line of action, the objectives of the present study were to analyze the Brazilian national scientific production, focusing on the entrepreneurial characteristics of Brazilian nursing, and to formulate and validate a theoretical-methodological entrepreneurial management technology for nursing. Methodology: Methodological study based on an integrative review and the theoretical-practical experience of experts recognized by their peers as entrepreneurs. The integrative review consisted of data collection, between April and June 2018, in the Latin American and Caribbean Literature on Health Sciences (LILACS), the Scientific Electronic Library Online (SciELO), and the Nursing Database of the Virtual Health Library (BDENF, as per its acronym in Portuguese) databases. The search was carried out with the descriptors “entrepreneurship” and “nursing”, with no preestablished time interval because of the limited number of publications in this area. The search resulted in 19 articles, selected according to inclusion and exclusion criteria previously defined. In the second phase of the study, developed between June and September 2018, the development of the theoretical-methodological entrepreneurial management technology and the content validation of its dimensions and items were carried out. In this validation process, experts were considered professionals who had a vast theoretical-practical experience in management and entrepreneurship. To identify experts, in addition to applying the snowball referral technique, a search in the Currículo Lattes platform was performed to determine whether their profile fitted the characteristics desired in the present study. This process resulted in the identification of 14 experts, of whom 11 accepted to participate in the investigation. Results: The results of the integrative review step showed that entrepreneurship in the nursing area has gained prominence in the past years and that its entrepreneurial characteristics are centered in the social, business, and training domains. Regarding the methodological examination, although the items of the instrument were described in clear and objective scientific language so as to allow the understanding of its content by any nursing or health professional, some terms raised doubts and required adjustments. At the end of the validation process of the entrepreneurial management technology, 90% of agreement were obtained in all the items. Additionally, all the items were validated as pertinent and considered prospective to professionals who wish to start a business and explore new opportunities, goods, and services in the nursing and health area. Final considerations: Entrepreneurship in the nursing area has gained prominence in the past years. Nursing can be pointed out as one of the professions that have most discussed the subject of entrepreneurship in the health sciences area, although the process is still incipient and small. The theoretical-methodological technology on entrepreneurial management had all its items validated by experts and can be used in training and care settings and mainly by professionals who wish to feature differentiated technologies or enterprises in the nursing and health scope. Regarding the limitations of the present study, the few and recent thematic investigations on entrepreneurial management and validated theoretical-methodological processes on the subject in the nursing and health area stand out. Consequently, the discussion of results had to resort, almost exclusively, to studies from economic and social sciences. It is suggested that new investigations are designed to validate the phases or steps related to the entrepreneurial process in the nursing and health area more broadly and based on national and international scientific evidence. Regarding the product and its applicability: The theoretical-methodological technology on entrepreneurial management in maternal and children’s health, validated by experts, can be used in training and care settings and mainly by professionals who wish to feature new knowledge and practices in the organization and management sphere. Additionally, the technology will contribute to discussions on entrepreneurship theory and the coordination between the knowledge originated in the academia and the entrepreneurial experience by integratin